PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO PADA MATA PELAJARAN EKONOMI - Eka Diana Ferianti; Sudarman; Sutrisno (Jurnal Prospek: Pendidikan Ilmu Sosial dan Ekonomi, 2024)
From this research, it was found that there were obstacles in implementing the learning process, namely, the lack of utilization of video learning media used at SMA Negeri 3 Samarinda. This is because in the learning process teachers mostly use lecture or power point methods as learning media. The methods used by the ASSURE model are Analyze Learner, State Standards and Objective, Select Strategies, Technology, media or materials, Utilize Technology, Media and Materials, Require Learned Participation, and Evaluate and Revise. Based on the results of this research, all stages carried out by researchers in developing this video learning media produced valid media based on expert assessments. Media experts gave a total score of 40 out of 45 with an eligibility percentage of 89.9%, so this video learning media was declared "Very Appropriate" for use. The material expert also gave a total score of 60 out of 65 with a feasibility percentage of 98.8%, so this video learning media was also declared "Very Appropriate" for use.